2002
DOI: 10.1038/sj.bjc.6600233
|View full text |Cite
|
Sign up to set email alerts
|

Cimetidine modulates the antigen presenting capacity of dendritic cells from colorectal cancer patients

Abstract: Cimetidine, a H 2 receptor antagonist, has been reported to improve survival in gastrointestinal cancer patients. These effects have largely been attributed to the enhancing effects of cimetidine on the host's antitumour cell-mediated immune response, such as inhibition of suppressor T lymphocyte activity, stimulation of natural killer cell activity and increase of interleukin-2 production from helper T lymphocytes. We conducted an in vitro study on the effects of cimetidine on differentiation and antigen pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Cimetidine has demonstrated immunomodulatory effects in a number of studies (32)(33)(34)(35)(36), while histamine has been shown to have immunosuppressive effects (37,38). These results suggest that the effect of cimetidine on immunity is mediated by blocking the immunosuppressive effect of histamine via the H 2 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Cimetidine has demonstrated immunomodulatory effects in a number of studies (32)(33)(34)(35)(36), while histamine has been shown to have immunosuppressive effects (37,38). These results suggest that the effect of cimetidine on immunity is mediated by blocking the immunosuppressive effect of histamine via the H 2 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Since circulating T lymphocytes and NK cells are major defense mechanisms against tumor cells released into the circulation, and TIL is one of the most crucial factors restricting local tumor growth and progression, it is desirable to use it as an immunomodulator in the perioperative period. Moreover, since CIM has many other favorable effects besides immunomodulation on lymphocytes, such as activating macrophages, increasing tumor inhibitory cytokines [49] , enhancing the antigen presenting capacity of dendritic cells [60] , reducing tumor cell proliferation, inhibiting tumor cell metastasis via anti-adhesion mechanisms [49] and increasing the overall survival of colorectal cancer patients with high levels of sialyl Lewis-X and sialyl Lewis-A epitope expression on tumor cells [61] , it is therefore advisable to use this low cost, convenient and almost nontoxic drug as a practical immunity-enhancing measure for GI cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…An accumulating body of evidence suggests that this drug may improve the survival of patients with different malignancies, and its antitumor effect is mediated at least in part by immune mechanisms. In particular, cimetidine-mediated immunomodulation is based on the the enhancement of antigen-presenting DC activity, 113 inhibition of suppressor T lymphocyte activity 114 and MDSC activity, 115 stimulation of NK cell activity 116 and increase in IL-2 production in helper T lymphocytes. 117 Another H2-antagonist famotidine has been found to stimulate IL-2-driven LAK activity beneficial for the treatment of renal cancer.…”
Section: Inhibitors Of Indoleamine 23-dioxygenase (Ido)mentioning
confidence: 99%